The provision point mechanism with reward money - Robertas Zubrickas (University of Zurich, Department of Economics, 2013)
We introduce reward money into the provision point mechanism with refunds. Reward money is distributed among the contributors in proportion to their contributions only when the provision point is not reached. In environments without aggregate uncertainty, the provision point is always reached in equilibrium as competition for reward money and preference for the public good induce sufficient contributions. Importantly, the mechanism not only ensures allocative efficiency but also distributional. At a specific level of reward money, we obtain a unique equilibrium, where all consumers contribute the same proportion of their private valuations. The advantages of the mechanism are also demonstrated for collective action problems.
Keywords: D82; H41; 330; public goods; private provision; provision point mechanism; distributional efficiency; collective action problem; Öffentliche Güter; Allokation; Ökonomischer Anreiz; Verteilungswirkung; Asymmetrische Information; Entscheidungstheorie